Stretching the Iron Cage: The Constitution and Implications of Routine Workplace Resistance - Prasad, Pushkala; Prasad, Anshuman (Organization Science, 2000)
Organizational scholars have shown considerable interest in the rise of complex systems of organizational control, sometimes referred to metaphorically as the process of tightening the iron cage, as well as patterns of workplace resistance to it. More recently, the scholarly spotlight seems to have shifted from formal modes of employee resistance to more informal or routine forms of workplace resistance. This paper presents a detailed ethnographic account of informal resistance and its ability to limit managerial control in a health maintenance organization undergoing the computerization of its administrative functions. Our study adopts a more problematic approach to understanding routine resistance, tracing its discursive constitution in the workplace. Using the findings of an ethnographic study involving observation and interviews, we show how routine resistance was discursively constituted and how it limited organizational control in interesting and unexpected ways. This discursive constitution was achieved through (a) owning resistance, (b) naming resistance, and (c) designating indirect resistance. The paper also analyzes how these different discursive constructions limited managerial control by affirming autonomous self-identities, renegotiating roles and relationships, and reinterpreting dominant managerial discourses. Finally, broader implications for understanding routine resistance in organizations are drawn.